Smart Digital Technology Affects the Efficiency of Water Management of Royal Irrigation Department - Tannarat, Thanat; Ratanaset, Walaiporn (Journal of Dhamma for Life, 2026)
This study aimed to investigate: (1) the level of personnel opinions toward smart digital technologies in water management within the Royal Irrigation Department (RID); (2) the level of water management efficiency; (3) the relationship between personnel opinions toward smart digital technologies and water management efficiency; and (4) the smart digital technology factors affecting water management efficiency. This quantitative research employed a sample of 243 RID civil servants, determined using Yamane’s formula and selected through stratified random sampling. Data were collected using a questionnaire and analyzed through frequency, percentage, mean, standard deviation, Pearson’s correlation coefficient, and multiple regression analysis. The findings revealed that: (1) personnel opinions toward smart digital technologies were at a high level overall (x̄ = 4.19, S.D. = 0.48). Among the dimensions, attitude toward technology use had the highest mean score, while awareness and training had the lowest. In addition, smart digital technology factors were rated at a high level overall (x̄ = 4.13, S.D. = 0.58), with the Smart Water Operations Center receiving the highest mean score and the Central Database the lowest. (2) Water management efficiency was also rated at a high level overall (x̄ = 4.17, S.D. = 0.58), with resource utilization showing the highest mean score, while work quantity had the lowest. (3) Personnel opinions toward smart digital technologies were positively correlated with water management efficiency at the 0.05 level of statistical significance, with work quality demonstrating the strongest relationship (r = 0.700). (4) Five smart digital technology factors significantly affected water management efficiency at the 0.05 level of significance and jointly explained 76.80% of the variance in water management efficiency (R² = 0.768). This indicates that smart digital technology factors have a substantial influence on water management efficiency, highlighting the importance of systematic technology development alongside personnel development and capacity building.